If the question is (x-5)/-2 = (x-1)/3 then the answer would be as shown below
first cross multiply to get -2(x-1) = 3(x-5)
then distribute -2x+1 = 3x-15
move over the -2x by adding 2x to both sides and move -15 by adding 15 to both sides... this gives you 16 = 5x
divide both sides by 5 to get x = 16/5
*** if the problem is x-(5/-2) = x-(1/-3) then see below for the answer and explanation
this is not a possible question as anything you plug in for x will simplify to an unequal equation, plug in zero and get -(5/-2)=-(1/-3) this is not true so can not be possible